Pengaruh Model Discovery Learning Terhadap Minat Dan Hasil Belajar Matematika Peserta Didik Kelas VIII MTS Di Malunda - Yahya, Amran; Zafitri, Gita; Muliana M, Ana; Bahasa Indonesia, Bahasa Indonesia (Jurnal PEKA (Pendidikan Matematika), 2024)
The aim of the research is to find out what students’ interests and learning outcomes are who use the Discovery Learning model is higher than interest and learning outcomes of students who use conventional learning models. This type of quasi-experimental research with a pretest posttest nonequivalent control design group design. This research was carried out at MTs DDI Malunda for the 2023/2024 academic year. Where class VIII B is the experimental class and class VIII A is the control class with a saturated sampling technique. Data collection using questionnaires, test and observation sheets on the implementation of learning by teachers and students. Data analysis techniques use descriptive and inferential analysis. Descriptive analysis the average score of the experimental class posttest questionnaire (89.96), the average score of the posttest questionnaire control class (75.69). For the average test score for the experimental class (86.53), while the score control class posttest average (61.23). Results show interest and learning outcomes mathematics students are taught using the Discovery Learning model more high compared to the interest and mathematics learning outcomes of the students being taught using conventional learning models. To test the hypothesis used are the T-Test and ManovaTest with sig values. Students’ interest in learning mathematics (0.000<0.05) and obtained a sigvalue. Student learning out comes (0.000<0.05) means H1 accepted. The conclusion is that students’ interests and learning outcomes in mathematics are using the Discovery Learning model is higher than interest and mathematics learning out comes of students who use the learning model conventional.